Битва з татарами під Мартиновим 1624 р. - Тимів, І. (Сiверянський лiтопис, 2016)
У статті розглянуто політичні передумови та обставини татарського вторгнення на територію Руського воєводства ногайських татар на чолі із Кантеміром-мурзою в червні 1624 р., з’ясовано стан вивчення цієї події у вітчизняній і польській історіографії, висвітлено джерельну базу проблеми, розглянуто приготування польсько-українських сил під орудою польного гетьмана Станіслава Конецпольського до генерального бою під Мартиновим 20 червня 1624 р. У хронологічній послідовності автор показав хід дій польської армії і ногайського війська, починаючи від 4 до 22 червня 1624 р. У додатках до статті подано поіменний перелік панів-волонтерів, які зі своїми загонами брали участь у битві під Мартиновим. У тому ж реєстрі зазначено список татарських мурз, учасників баталії. В статье рассмотрены политические предпосылки и обстоятельства татарского вторжения на территорию Русского воеводства ногайских татар во главе с Кантемиром-мурзой в июне в 1624 г., выяснено состояние изучения этого события в отечественной и польской историографии, отражены источники битвы, рассмотрено приготовление польско-украинских сил под руководством польного гетмана Станислава Конецпольского к генеральному бою под Мартыновым 20 июня в 1624 г. В хронологической последовательности автор показал ход действий польской армии и ногайского войска, начиная от 4 до 22 июня 1624 р. У приложениях к статье подан поименный перечень господ-волонтеров, которые со своими отрядами участвовали в битве под Мартыновым. В том же реестре отмечен список татарских мурз, участников баталии. The article represents the political background and the circumstances of the Tatar invasion, headed by Kantymir Murza, to the territory of Ruska Province of the Nogais in June 1624. It’s found out the condition of this event investigation in the domestic and Poland historiography. The base of the problem is showed. It is represented the preparation of the Polish and Ukrainian forces, headed by the hetman Stanislav Konetspolskiy, to the main struggle near Martyniv on the 20th of June 1624.The Polish army and the Nogai Horde actions are represented in the chronological sequence, beginning with the 4th to the 23rd of June 1624. It is highlighted the actions of the assailants and defenders of the region during the Horde invasion. The region, occupied by the invasion, is also mentioned. The article also retraces the Tatar return from the campaign. The main stages, consequences and the importance of the battle near Martyniv are studied. It’s determined that the Polish troops’ actions were more organized and coordinated. Due to it and the well-thought out and realized tactics, the success of the Polish and Ukrainian forces, in the battle near Martyniv was insured. The appendixes to the article include the list of the gentlemen’s names who were the volunteers and together with their troops took part in the battle near Martyniv. The same list includes the Tatar murzas’ names who were the participants of the battles.